Effects of Collard Green Consumption on the Human Plasma and Urine Metabolome: An Untargeted Analysis. (29th May 2020) - Bouranis, John; Beaver, Laura; Choi, Jaewoo; Kelly, Jennifer; Booth, Sarah; Stevens, Jan; Ho, Emily
Abstract: Objectives: Whereas phytochemicals derived from cruciferous vegetables have demonstrated health benefits, the data linking intake of these vegetables to health outcomes are inconsistent. These inconsistencies may stem from methodological limitations in accurately assessing cruciferous vegetable exposure. Goals of this study were to explore the use of endogenously deuterium-labeled collard greens combined with untargeted metabolomics to identify unique plant-derived and host-derived metabolites following vegetable consumption as potential biomarkers of cruciferous vegetable intake in humans. Methods: 26 participants (16 women, 10 men) were fed a breakfast including 100 g of collard greens grown with or without deuterium-labeled water. Plasma was sampled prior to ingestion and 4 h post-ingestion; 24 h urine samples were also collected. High-pressure liquid chromatography Triple Q-ToF mass spectrometry-based untargeted metabolomics was performed. Results: Analysis of collard greens confirmed deuterium-labeled compounds, including glucosinolates (glucobrassicin, sinigrin), and flavonols (quercetin). The maximum abundance of stable isotopologues was 2 H4 (M4 ) for glucobrassicin and 2 H12 (M12 ) for 1, 2, 2'-trisinapoylgentiobiose. Consumption of collard greens was associated with a significant increase in 199 compounds in plasma, including a 5.26-fold increase in the antioxidant hydroferulic acid ( q < 0.05). A significant decrease in 144 compounds in plasma was also found with collard green consumption. Likewise, a significant increase in 819 compounds and decrease in 1209 compounds was found in urine following collard green consumption. A deuterium labeled 18-carbon fatty acid was significantly increased in plasma, indicating it was derived from the collard greens. Work is ongoing to further identify deuterium-labeled plant derived compounds in human plasma and urine. Conclusions: Consumption of a cruciferous vegetable changed the urine and plasma metabolome. Ongoing research is required to identify these metabolites in order to develop novel signatures of food intake. Funding Sources: National Institutes of Health, United States Department of Agriculture Agricultural Research Service, National Institute of Food and Agriculture.